1955
DOI: 10.1002/hlca.19550380106
|View full text |Cite
|
Sign up to set email alerts
|

Komplexbildner als Cofaktoren isolierter Zellgranula

Abstract: 1) Stickstoffwerte stets zu niedrig; die Substanz ist sehr schwer verbrennbar. . l) Verwendete Abkurzungen: A T P : Adenosintriphosphat; Komplexon: Athyleridiamin-tetraacetat (= Komplexon I11 der AG. B. Xie3jried, im angelsachsisehen Schrifttum auch EDTA oder versene genannt); Gl!/kolkomplexon: Verbindung V der Tab. 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

1955
1955
1972
1972

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 12 publications
3
55
0
Order By: Relevance
“…Light-scattering: The optical density at 520 my decreased linearly with increasing sucrose or glucose concentrations, in contrast to what is commonly found in mitochondria (24). Changes in optical density are not necessarily an indication of volume change (28) but may also be due to changes in the refractive indices of either the particles or the dispersing medium (3).…”
Section: Chemical Analysis Of Washed Native-fatmentioning
confidence: 97%
See 1 more Smart Citation
“…Light-scattering: The optical density at 520 my decreased linearly with increasing sucrose or glucose concentrations, in contrast to what is commonly found in mitochondria (24). Changes in optical density are not necessarily an indication of volume change (28) but may also be due to changes in the refractive indices of either the particles or the dispersing medium (3).…”
Section: Chemical Analysis Of Washed Native-fatmentioning
confidence: 97%
“…Weights were corrected for the occluded sucrose by the method of Trevelyan and Harrison (30). B: Light-scattering was measured spectrophotometrically at 520 m/A by the methods of Cleland (6) and Raaflaub (24). C: Viscosity was determined after dialysis in the cold to equilibrium against various sucrose concentrations.…”
mentioning
confidence: 99%
“…Additional evidence for the above mentioned interpretations came from observations on changes in low amplitude light scattering and optical density (12-16), which accompanied the "energy states" described by Chance and Williams (17) . Reports (18)(19)(20)(21)(22)(23) appeared previously which showed that energy transduction in the mitochondrion included not only oxidative phosphorylation and active transport but also mechanochemical processes . Other mechanochemical studies have shown that energy derived from ATP (24) or from electron transport (25,26) can drive mitochondrial contraction .…”
Section: Introductionmentioning
confidence: 99%
“…The swelling of isolated mitochondria in response to the introduction of orthophosphate (Pi) to the suspending medium has been studied in a number of works (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) . In particular, Packer (11) found the P ; induced swelling to be dependent on the presence of state 4 and to be reversed upon the induction of state 3 .…”
Section: Introductionmentioning
confidence: 99%